(untitled) (Research, Society and Development, 2020)
Attapulgite is a phyllosilicate from the group of fibrous clay, complex magnesium and aluminium silicate characterized by their elongated form. Due to the arrangement and fine granulometry, attapulgite has a high surface area and high adsorption capacity. These properties justify the growing interest of its use in facial masks, because phyllosilicates allow the adsorption of dirt from the skin and promote a slight physical exfoliation, removing dead cells. The present study aimed to develop and characterize peel-off facial masks based on attapulgite. For this, different concentrations of attapulgite (0 - 2%) were used, followed by organoleptic evaluation, determination of viscosity and pH, spreadability, centrifugation test and drying time test. It was observed that the formulations have a homogeneous and firm appearance and are compatible with the cutaneous pH. The relative densities of the masks were higher than that of distilled water but did not imply restrictions on the application of any of the samples. In addition, the spreadability was similar between the different formulations. No sample showed phase separation in the centrifuge test, indicating good stability. It was evaluated that the attapulgite content influenced the drying time of the masks, after which it was possible to completely remove the formed films. It was concluded that, although all formulations presented pH, density and physical stability suitable for facial application, samples F3 (1.5%, m/m) and F4 (2.0%, m/m) had a shorter drying time, an important aspect for the type of mask developed. On the other hand, these formulations have slightly lower spreadability compared to other masks, due to the crosslinking effect that phyllosilicates have in polymeric matrices. Therefore, attapulgite, a natural phyllosilicate, inexpensive, widely available and biocompatible, it can be used in dermocosmetic formulations, such as peel-off masks, which meet the requirements quality and suitability for the intended use.